Объяснение:
–(2x+3)²+(x+5)(2x+5)=16
–(4х²+12х+9)+(2х²+5х+10х+25)=16
–4х²–12х–9+2х²+5х+10х+25=16
–2х²+3х+16=16
–2х²+3х=0
а=–2;
b=3
с=0
Д= 3²–4*(–2)*0= 9–0= 9
х(1)=
х(2)=
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Объяснение:
–(2x+3)²+(x+5)(2x+5)=16
–(4х²+12х+9)+(2х²+5х+10х+25)=16
–4х²–12х–9+2х²+5х+10х+25=16
–2х²+3х+16=16
–2х²+3х=0
а=–2;
b=3
с=0
Д= 3²–4*(–2)*0= 9–0= 9
х(1)=![\frac{ - 3 + \sqrt{9} }{ - 4} = \frac{ - 3 + 3}{ - 4} = 0 \frac{ - 3 + \sqrt{9} }{ - 4} = \frac{ - 3 + 3}{ - 4} = 0](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%203%20%2B%20%20%5Csqrt%7B9%7D%20%7D%7B%20-%204%7D%20%20%3D%20%20%5Cfrac%7B%20-%203%20%2B%203%7D%7B%20-%204%7D%20%20%3D%200)
х(2)=![\frac{ - 3 - \sqrt{9} }{ - 4} = \frac{ - 3 - 3}{ - 4} = \frac{ - 6}{- 4} = \frac{3}{2} = 1.5 \frac{ - 3 - \sqrt{9} }{ - 4} = \frac{ - 3 - 3}{ - 4} = \frac{ - 6}{- 4} = \frac{3}{2} = 1.5](https://tex.z-dn.net/?f=%20%5Cfrac%7B%20-%203%20-%20%20%5Csqrt%7B9%7D%20%7D%7B%20-%204%7D%20%20%3D%20%20%5Cfrac%7B%20-%203%20-%203%7D%7B%20-%204%7D%20%20%3D%20%20%5Cfrac%7B%20-%206%7D%7B-%204%7D%20%20%3D%20%20%5Cfrac%7B3%7D%7B2%7D%20%20%3D%201.5)